2021
DOI: 10.48550/arxiv.2108.06233
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Simultaneously Transmitting and Reflecting (STAR) Intelligent Omni-Surfaces, Their Modeling and Implementation

Abstract: With the rapid development of advanced electromagnetic manipulation technologies, researchers and engineers are starting to study smart surfaces that can achieve enhanced coverages, high reconfigurability, and are easy to deploy. Among these efforts, simultaneously transmitting and reflecting intelligent omni-surface (STAR-IOS) is one of the most promising categories. Although pioneering works have demonstrated the benefits of STAR-IOSs in terms of its wireless communication performance gain, several important… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…For (8), by exploiting (1)-( 5), it can be shown that the complex-valued T&R coefficients of the passive STAR-RIS elements have to satisfy…”
Section: B Correlated Tandr Phase-shift Modelmentioning
confidence: 99%
See 4 more Smart Citations
“…For (8), by exploiting (1)-( 5), it can be shown that the complex-valued T&R coefficients of the passive STAR-RIS elements have to satisfy…”
Section: B Correlated Tandr Phase-shift Modelmentioning
confidence: 99%
“…To investigate the impact of the proposed correlated T&R phase-shift model given in (8) on wireless system performance, we consider a STAR-RIS-aided two-user downlink system, as illustrated in Fig. 3.…”
Section: System Modelmentioning
confidence: 99%
See 3 more Smart Citations